Urban Social Listening Potential and Pitfalls for Using Microblogging Data in Studying Cities - Hollander, Justin B.; Graves, Erin.; Renski, Henry; Foster-Karim, Cara.; Wiley, Andrew; Das, Dibyendu; SpringerLink (Online service) (London : Palgrave Macmillan UK(Imprint), 2016)
This book analyses new software tools and social media data that can be used to explore the attitudes of people in urban places. It reports on the findings of several research projects that have have experimented with using microblogging data in conjunction with diverse quantitative and qualitative methods, including content analysis and advanced multivariate statistics. Applied researchers, planners and policy makers have only recently begun to explore the potential of Big Data to help understand social attitudes and to potentially inform local policy and development decisions. This book provides an original analysis into how Twitter can be used to describe the urban experience and people's perception of place, as well as offering significant implications for public policy. It will be of great interest to researchers in human geography, social media, cultural studies and public policy. Justin B. Hollander is Associate Professor of Urban and Environmental Policy and Planning, Tufts University, USA. Erin Graves is Senior Policy Analyst at the Federal Reserve Bank of Boston, USA. Henry Renski is Associate Professor, Department of Landscape Architecture and Regional Planning, University of Massachusetts Amherst, USA. Cara Foster-Karim is a graduate of the Urban and Environmental Policy and Planning Program, Tufts University, USA. <dibyendu das="" is="" a="" graduate="" student="" in="" electrical="" engineering="" at="" tufts="" university,="" usa.
Chapter 1. Introduction -- Chapter 2. A Short History of Big Data Analysis -- Chapter 3. Taking Microblogging Data for a Test Drive -- Chapter 4. A Close Look at Urban Immigrant Communities -- Chapter 5. A National Comparison: Twitter vs. The American Housing Survey -- Chapter 6. Conclusion.
Keywords: Social media; Internet marketing; Environmental sociology; Human geography